A Cooperative Switching Algorithm for Multi-Agent Foraging. (April 2016) - Zedadra, Ouarda; Seridi, Hamid; Jouandeau, Nicolas; Fortino, Giancarlo
Abstract: The foraging task is one of the canonical testbeds for cooperative robotics, in which a collection of robots have to find and transport one or more objects to specific storagepoints. Efficiency in foraging can be improved with coordinated team of robots. Swarm robotics investigates the bio-inspired behaviors of simple species, that provide complex behaviors at the group level. We present a multiagent foraging algorithm named Cooperative Switching Algorithm for Foraging (C-SAF) inspired from the classical ant system. It provides a quick search, optimal homing paths and quick exploitation of food. A qualitative comparison between some foraging related works and the proposed algorithm is given here, as well as a quantitative comparison which shows that our algorithm outperforms the reference c-marking algorithm across a range of different scenarios.